2000
DOI: 10.1128/jb.182.6.1641-1649.2000
|View full text |Cite
|
Sign up to set email alerts
|

Substrate Specificity of Naphthalene Dioxygenase: Effect of Specific Amino Acids at the Active Site of the Enzyme

Abstract: The three-component naphthalene dioxygenase (NDO) enzyme system carries out the first step in the aerobic degradation of naphthalene by Pseudomonas sp. strain NCIB 9816-4. The three-dimensional structure of NDO revealed that several of the amino acids at the active site of the oxygenase are hydrophobic, which is consistent with the enzyme's preference for aromatic hydrocarbon substrates. Although NDO catalyzes cis-dihydroxylation of a wide range of substrates, it is highly regio-and enantioselective. Site-dire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
135
0
2

Year Published

2001
2001
2016
2016

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 182 publications
(143 citation statements)
references
References 60 publications
6
135
0
2
Order By: Relevance
“…The crystal structure also showed that the alternative NDO substrate indole binds near the mononuclear iron, suggesting that this is the oxygen-activating site (12). In support of this proposal, site-directed mutagenesis studies on NDO demonstrated that substitution of the hydrophobic residues lining the substrate binding pocket alter both the stereo-and regioselectivity of NDO (13). Also, the ligands of the mononuclear iron are one solvent, two histidines and one bidentate aspartic acid forming a 2-His 1-carboxylate "facial triad," as observed in many other O 2 -activating iron-containing enzymes (14,15).…”
mentioning
confidence: 53%
“…The crystal structure also showed that the alternative NDO substrate indole binds near the mononuclear iron, suggesting that this is the oxygen-activating site (12). In support of this proposal, site-directed mutagenesis studies on NDO demonstrated that substitution of the hydrophobic residues lining the substrate binding pocket alter both the stereo-and regioselectivity of NDO (13). Also, the ligands of the mononuclear iron are one solvent, two histidines and one bidentate aspartic acid forming a 2-His 1-carboxylate "facial triad," as observed in many other O 2 -activating iron-containing enzymes (14,15).…”
mentioning
confidence: 53%
“…This amino acid corresponds to Thr-351 in the large subunit of naphthalene dioxygenase. However, the change of Thr-351 to Asn in naphthalene dioxygenase had a minor effect on product formation (32).…”
Section: Discussionmentioning
confidence: 99%
“…Substitiution of valine or leucine for Phe-352 near the active site iron in the ␣-subunit of NDO altered the stereochemistry of naphthalene cis-dihydrodiol formed from naphthalene and also changed the region of oxidation of biphenyl and phenanthrene (473,475).…”
Section: Enzymatic Upgrading Of Petroleum Fractions and Pure Hydrocarmentioning
confidence: 99%